2014
DOI: 10.3233/ifs-130768
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy based assessment method for comparison of ship launching methods

Abstract: In a shipyard production system, launching operation is vital process since launching stage is time consuming process as well as being high cost. Therefore, this is a significant issue for shipyards. Choosing the most appropriate one among launching methods gives an advantage to shipyards to obtain competitive power against their competitors. If this is done, shipyards can commit to delivery of more ships and make more profit. In this study, launching methods are evaluated in terms of various performance crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Acta Scientiarum. Technology, v. 43, e51796, 2021 Also, we can see that the results are consistent with the existing literature, since Ozkok and Cebi (2014) in their work, which aimed to make a general analysis of all types of launching methods from of a SWOT analysis, multicriteria decision methods (MCDM) and fuzzy logic, concluded that dry dock and airbag options are considered the most appropriate launching methods in terms of cost, performance and risk factors. The authors further state that the airbag method is emerging in far east shipyards and it is believed that those who prefer the use of dry dock or airbag launching will benefit from a substantial gain related to competitive power.…”
Section: Discussionsupporting
confidence: 85%
“…Acta Scientiarum. Technology, v. 43, e51796, 2021 Also, we can see that the results are consistent with the existing literature, since Ozkok and Cebi (2014) in their work, which aimed to make a general analysis of all types of launching methods from of a SWOT analysis, multicriteria decision methods (MCDM) and fuzzy logic, concluded that dry dock and airbag options are considered the most appropriate launching methods in terms of cost, performance and risk factors. The authors further state that the airbag method is emerging in far east shipyards and it is believed that those who prefer the use of dry dock or airbag launching will benefit from a substantial gain related to competitive power.…”
Section: Discussionsupporting
confidence: 85%
“…In this process, at first all strategies (ST, SO, WT and WO) are determined in SWOT matrix, then they prioritize as the output of AHP or ANP process. Like combination of TOPSIS Iran's stock market Hatami and Saati (2009) Cosmetics organization Alptekin (2013) Furniture firm Ozkok and Cebi (2014) Shipyard production system Forest (Agroforestry-Rwanda) Ebonzo and Liu (2013) Applied AFS (axiomatic fuzzy set theory) and implemented in the case of (Yuksel & deviren. 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ozkok and Cebi 48 proposed an integrated method including AHP, fuzzy information axiom (FIA), technique for order performance by similarity to ideal solution (TOPSIS) and SWOT analyses to evaluate and determine the dry docking technique as the most convenient launching method with respect to the conflicting criteria.…”
Section: Questionsmentioning
confidence: 99%